Pengembangan Program Pelatihan Teknik Penulisan Modul Untuk Widyaiswara BPSDM Provinsi DKI Jakarta - Putri Purwaning; Retno Widyaningrum; Cecep Kustandi (Jurnal Pembelajaran Inovatif, 2019)
This development research aims to develop an appropriate training program about module writing which intended to the Instructors of BPSDM Jakarta in order to increase ones’ knowledge and competencies in module writing. The program development refers to the Instructional Development Model by M. Atwi Suparman. Basde on these models, research and developmenta has been through the stages of assess needs to identify instructional goal, conduct instructional analysis, analyze learners and contexts, write performance objectives, develop assessment instrument, develop instructional strategy, develop and select instructional, and design and conduct formative evaluation. This research also developed a book of training program for Instructors, training module, and presentation media, in order to assist the training process. The evaluation of the training program includes two phases which consist of expert review and one-to-one evaluation. The evaluation scores from expert review phase by Instructional Design Expert is 3.73 which considered as very good, also the scores from media expert for learning source module is 3.88 which considered as very good and for presentation media 3.17 which considered as very good either. The one-to-one evaluation phase involved 3 Instructors and the scores obtained is 3 which considered as good. Based on the results of evaluation, it can be concluded that this training program is appropriate to be implemented in order to increase the competencies of module writing for the Instructors of BPSDM DKI Jakarta.